Uwarunkowania zmian administracji publicznej : uwagi ogólne - Kalisiak-Mędelska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Presently, the public administration faces many problems which make its activity more difficult. There are also many serious challenges it is confronted with. Although the system of public administration has changed since 1990's it is still inefficient from the organizational and financial point of view. Moreover, it is not prepared to adapt modern methods of management. According to specialists, the methods used by the administration presently do not guarantee its professionalism. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 658-663